The Effect of Temperature and Aging Time on The Micro Structure and Hardness of Ni-Al-Ti-Ge Alloy - Djoko Hadi Prajitno; Pradoto Ambardi; Misdarlila Misdarlila (Jurnal Metal Indonesia, 2022)
Intermetallic alloy is a combination consists of two metal compounds or more. One of intermetallic alloy that can be used is nickel. Nickel is a corrosion resistant metal and withstands high temperature. Intermetallic alloy can be used for application on aircraft components such as turbin gas engine that operate in high temperature and extreme environment. This study is conducted to find out the changes of micro structure and hardness in NiAlTi material added by germanium of 1,5% as doping. In this study, heat treatment process was carried out with variation of temperature and aging time. The heat treatment included solution treatment and aging process. Solution treatment process was carried out at 1000oC  using tube furnace with holding temperature time for 2 hours. Aging process was carried out at 700oC, 800oC, 870oC  for 1, 2  and 3 hours for each temperature. Based on the hardness result, solution treatment heat treatment increase the grain size and also hardness of NiAlTi+1,5%Ge due to intermetallic compound formed in the alloy. Aging treatment increase the grain size and also hardness value. Maximum hardness take place at  870oC for 3 hours  with hardness of 45 HRc. Characterization by optical microscope and SEM showed that the alloy contain dendritic and interdendritic microstructure.  Examination by XRD and EDS shows that intermetallic compound formed in all NiAlTi+1,5%Ge specimens are dominated by intermetallic of Ni3Al (Ɣ’).